Biological evaluation of some quinoline derivatives with different functional groups as anticancer agents - Koprulu, Tugba Kul; Okten, Salih; Tekin, Saban; Cakmak, Osman (WILEY, 2019)
Due to a great deal of biological activities, quinoline derivatives have drawn attention for synthesis and biological activities in the search for new anticancer drug development. In this work, a variety of substituted (phenyl, nitro, cyano, N-oxide, and methoxy) quinoline derivatives (3-13) were tested in vitro for their biological activity against cancer cell lines, including rat glioblastoma (C6), human cervical cancer cells (HeLa), and human adenocarcinoma (HT29). 6-Bromo-5-nitroquinoline (4), and 6,8-diphenylquinoline (compound 13) showed the greatest antiproliferative activity as compared with the reference drug, 5-fluorouracil (5-FU), while the other compounds showed low antiproliferative activity. 6-Bromo-5-nitroquinoline (4) possesses lower cytotoxic activity than 5-FU in HT29 cell line. Due to its the apoptotic activity 6-Bromo-5-nitroquinoline (4) has the potential to cause cancer cell death.
Keywords: apoptosis; cancer cells; cytotoxic activity; nitroquinoline; phenylquinoline; quinolines; 8-SUBSTITUTED QUINOLINES; BROMINATION; Biochemistry & Molecular Biology; Toxicology